Health insurance inequity in selected Asia countries - M. R., Izzanie; Khaled, Nada; M., Aidalina (Community Health Society Malaysia, 2019)
Background: Health insurance is the primary mechanism that enables people to obtain healthcare services. There are three major types of health insurance involves private health insurance, social health insurance and community-based health insurance. Aims: This systematic review aims to identify the implication on equity after implementation of health insurance focusing on selected Asian countries. The review is based on the three dimensions of universal health coverage (UHC): population coverage, and service coverage and financial coverage. Materials and methods: A systematic search for articles was conducted form 4 searchengines, Scopus, Science Direct, Proquest, and Google scholar. A total of 13 articles wereselected after screenings and equity implications were concluded in three UHC dimensions based on equity index reported or equity improvement observed in time series studied. Result and discussion: All the three health insurance has different implication on equity between countries or within country. In terms of population coverage, SHI in Thailand showed an equitable coverage. Philippine also reported to have equitable population cover agein terms of geographical while in Vietnam, CBHI showed inequitable population coverage.The financial coverage has showed an inequity of CBHI in India, China, and Thailand. The inequity was also observed for SHI in Philippine, Vietnam and Philippines. More apparent is inequity in PHI for Malaysia and Philippines. The only equitable financial coverage reported was Thailand for its SHI. The final aspect is on service delivery coverage with equity has been observed in CBHI in China and SHI in Vietnam and Thailand. Conclusion: Social health insurance schemes can be further improved in addressing equity in all UHC aspects. CBHI of which showed some equitable measures for certain population subgroups, such as the poor, and formal workers can collectively be the way to go for SHI.